Comparative iTRAQ Proteomics Identified Myocardium Proteins Associated with Hypoxia of Yak - Babar, Asma; Mipam, Tserang D.; Wu, Shixin; Xu, Chuanfei; Shah, Mujahid Ali; Mengal, Kifayatullah; Yi, Chuanping; Luo, Hui; Zhao, Wangsheng; Cai, Xin; Luo, Xuegang (Current Proteomics, 2019)
Background: Yaks inhabit high-altitude are well-adapted to the hypoxic environments. Though, the mechanisms involved in regulatory myocardial protein expression at high-altitude were not completely understood. Objective: To revel the molecular mechanism of hypoxic adaptation in yak, here we have applied comparative myocardial proteomics in between yak and cattle by isobaric Tag for Relative and Absolute Quantitation (iTRAQ) labelling. Methods: To understand the systematic protein expression variations in myocardial tissues that explain the hypoxic adaptation in yak, we have performed iTRAQ analysis combined with Liquid Chromatography- Tandem Mass Spectrometry (LC-MS/MS). Bioinformatics analysis was performed to find the association of these Differentially Expressed Proteins (DEPs) in different functions and pathways. Protein to protein interaction was analyzed by using STRING database. Results: 686 Differentially Expressed Proteins (DEPs) were identified in yak with respect to cattle. From which, 480 DEPs were up-regulated and 206 were down-regulated in yak. Upregulated expression of ASB4, STAT, HRG, RHO and TSP4 in yak may be associated with angiogenesis, cardiovascular development, response to pressure overload to heart and regulation of myocardial contraction in response to increased oxygen tension. The up-regulation of mitochondrial proteins, ACAD8, GPDH-M, PTPMT1, and ALDH2, may have contributed to oxidation within mitochondria, hypoxia-induced cell metabolism and protection of heart against cardiac ischemic injuries. Further, the upregulated expression of SAA1, PTX, HP and MBL2 involved in immune response potentially helpful in myocardial protection against ischemic injuries, extracellular matrix remodeling and free heme neutralization/ clearance in oxygen-deficient environment. Conclusion: Therefore, the identification of these myocardial proteins in will be conducive to investigation of the molecular mechanisms involved in hypoxic adaptations of yaks at high-altitude condition.
Keywords: myocardium